2023
DOI: 10.3390/jcdd10030097
|View full text |Cite
|
Sign up to set email alerts
|

CPVT and Complete Atrio-Ventricular Block: The Flipside of the Same Coin

Abstract: Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) is a rare electrical genetic disease characterized by ventricular polymorphic tachycardia and/or bidirectional ventricular tachycardia induced by the release of catecholamines caused by intense physical or emotional stress in structurally normal hearts. Mostly, it is caused by mutations in genes that are involved in calcium homeostasis, in particular in the gene encoding for cardiac ryanodine receptor (RyR2). Our observation is the first description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Approximately 50–65% of CPVT-type 1 cases are associated with RYR2 gene mutation. Petrungaro et al found that CPVT can also give cardiac rhythm disturbances and be associated with overlap syndromes with non-compact myocardium in which patient presented with atrioventricular (AV) block ( 3 ). Although, intravenous adrenaline is the first choice of pharmaceutical therapy in cardiac resuscitation, the use of adrenaline in patient with RYR2 gene receptor mutation will lead to CPVT and death.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50–65% of CPVT-type 1 cases are associated with RYR2 gene mutation. Petrungaro et al found that CPVT can also give cardiac rhythm disturbances and be associated with overlap syndromes with non-compact myocardium in which patient presented with atrioventricular (AV) block ( 3 ). Although, intravenous adrenaline is the first choice of pharmaceutical therapy in cardiac resuscitation, the use of adrenaline in patient with RYR2 gene receptor mutation will lead to CPVT and death.…”
Section: Introductionmentioning
confidence: 99%